INTELLECTUAL CAPITAL, COMPETITIVE ADVANTAGE (EVIDENCE FROM INDONESIA’S MANUFACTURING SECTOR) - Merida, Peggy Delita (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2021)
The study aims to examine the direct relationship between intellectual capital and competitive advantage. The contribution of this paper is that there is a proxy competitive advantage the study was conducted on 444 manufacturing companies in Indonesia from 2013-2017. The novelty in this study is a research model that makes competitive advantage a dependent variable for intellectual capital and competitive advantage variables using market share proxy. The result of this study is intellectual capital has a positive effect on competitive advantage.